Development of abaca fiber-reinforced foamed fly ash geopolymer - Ngo, Janne Pauline S. (Animo Repository, 2018)
The growing environmental and economic concerns have led to the need for more sustainable construction materials. The development of foamed geopolymer combines the benefit of reduced environmental footprint and attractive properties of geopolymer technology with foam concrete's advantages of being lightweight, insulating and energy-saving. In this study, alkali-treated abaca fiber-reinforced geopolymer composites foamed with H2O2 were developed using fly ash as the geopolymer precursor. The effects of abaca fiber loading, foaming agent dosage, and curing temperature on mechanical strength were evaluated using Box-Behken design of experiment with three points replicated. Volumetric weight of samples ranged from 1966 kg/m3 to 2249 kg/m3. Measured compressive strength and flexural ranged from 19.56 MPa to 36.84 MPa, and 2.41 MPa to 6.25 MPa, respectively. Results suggest enhancement of compressive strength by abaca reinforcement and elevated temperature curing. Results, however, indicate a strong interaction between curing temperature and foaming agent dosage, which observably caused the composite's compressive strength to decline when simultaneously set at high levels. Foaming agent dosage was the only factor detected to significantly affect flexural strength. © The Authors, published by EDP Sciences, 2018.